Enhancing Collaborative Governance in Managing Grand Forest Park in Riau, Indonesia - Data Wardana; Mendra Wijaya; Raden Imam Al Hafis (Journal of Contemporary Governance and Public Policy, 2023)
This article discusses the management of the Riau Provincial Grand Forest Park from the perspective of collaborative governance. With its rich flora and fauna, Forest Park must be sustainably maintained and preserved as the ‘lungs’ of Pekanbaru City. However, limited human resources, regional financial capacity and the large area of land that must be managed are obstacles for local governments. It is therefore necessary to collaborate with various parties to set the initial conditions, institutional design, facilitation of leadership and processes for collaboration. This study employs a qualitative method with a phenomenological approach and describes collaboration events. The data collection techniques include observations, interviews and documentation. The study results show that the initial conditions are an obstacle for the government, requiring cooperation with other parties. Each party blindly covers the standards and provisions outlined in a joint agreement on the efforts and resources for the management of Forest Park facilitated by the Riau Provincial Forestry Service. The goals set for cooperation include the commitment of all parties to be transparent, mutually trusting and sustainable. This cooperation process was carried out in several stages, starting from the initial communication assessment, discussing existing problems and unifying the common perceptions outlined in the memorandum of understanding. Goals were established, action plans were formulated, and monitoring and evaluation were conducted on the results of the cooperation by each party. Collaboration was carried out in the form of the participation of all parties in preserving nature, including community involvement.